Capital Accumulation and Growth : A New Look at the Empirical Evidence - Fabio Schiantarelli; Asli Leblebicioglu; Steve Bond (Institute for the Study of Labor (IZA), 2004)
We present evidence that an increase in investment as a share of GDP predicts a higher growth rate of output per worker, not only temporarily, but also in the steady state. These results are found using pooled annual data for a large panel of countries, using pooled data for non-overlapping five-year periods, or allowing for heterogeneity across countries in regression coefficients. They are robust to model specifications and estimation methods. The evidence that investment has a long-run effect on growth rates is consistent with the main implication of certain endogenous growth models, such as the AK model.
Keywords: C23; E22; O40; 330; growth; capital accumulation; investment; Investition; Wirtschaftswachstum; Arbeitsproduktivität; Schätzung; Welt